Association of a mutation in the RUNX1 gene with the outcome of the disease in acute myeloid leukemia (meta-analysis) - M. L. Nikonorova; L. K. Kats (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article summarizes the data of a systematic review of scientific publications on acute myeloid leukemia over the past 10 years.The objective was to conduct a meta-analysis of the data published in the open press to investigate the nature of the association of mutations in the RUNX1 gene with the outcome of acute myeloid leukemia.Methods and materials. The search for publications was carried on library platforms eLibrary.ru, Google Academy, PubMed, Web of Science according to the criteria PRISMA 2020. The selection of studies was carried out using the Rayyan online program. The meta-analysis was performed on the basis of the RStudio application package. The main characteristics in the studies were reflected in overall survival, relapse-free survival, hazard ratio and were assessed by a standardized effect size. The magnitude of the effect was based on the difference between the observed patients and patients with mutations in the RUNX1 gene. The outliers filtering based on the combines confidence interval. The bias of publications was assessed visually and quantitatively.Results. The search identified 579 publications, 10 were included in the meta-analysis, the total sample was 2733 patients. The results of statistical tests on the Cochran Q-test (p-value < 0.0001) and the Higgens–Thompson test (92 %) indicate a high heterogeneity of the included publications. The variance of heterogeneity together with the 95 %CI (0.177; 1.528) indicates the heterogeneity of the research results. The combined 95 %CI (0.47; 2.90) does not suggest that mutations in the RUNX1 gene always lead to a poor prognosis. Egger’s regression test (p-value > 0.098) showed no publication bias.Conclusion. The results of the study revealed a statistical relationships between the influence of mutations in the RUNX1 gene and the outcome of the disease.